Pemberdayaan Masyarakat Melalui Pelatihan Pupuk Organik Dari Limbah Dapur - Amie Primarni; Chaira Saidah; Ika Kartika; Riyanto; Makmudi; Bela Oktavia; Vita Jamilah; Rahma Amelia; Muhammad Hafidz Baihaqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to empower the community of Sukmajaya Village Rt.5/Rw.5 through training in the production of organic fertilizer from kitchen waste. This training is expected to increase the knowledge, skills, and environmental awareness of the community in managing kitchen waste productively. This research uses a descriptive qualitative method with a case study approach, where data is collected through observation, in-depth interviews, and documentation. The results show that the training successfully improved the community's knowledge and skills in processing kitchen waste into organic fertilizer. The application of organic fertilizer to agricultural land had a positive impact on soil fertility and crop yields. Additionally, this training successfully increased environmental awareness and opened new economic opportunities for the community. However, challenges such as limited composting facilities and the need for ongoing assistance remain obstacles to the optimal implementation of this program. This research suggests continued support, infrastructure development, and market access to strengthen the positive impacts of this program in the future.